Bio-compatible fluorescent nano TiO materials prepared from titanium-oxo-cluster precursors. Issue 82 (27th September 2019) - Liu, Pei-Yi; Cui, Li-Na; Yang, Lei; Shu, Xian-Ping; Zhu, Qin-Yu; Dai, Jie
Abstract : Using a fluorescent dye pre-coordinated titanium-oxo-cluster (TOC) as a molecular precursor, a biocompatible and fluorescent nano TiO material was prepared, which opens the door for most non-water-soluble TOCs for the applications in biosystems. Abstract : Photoactive nano TiO2 particles with fluorescent properties have attracted great attention because of their potential applications in photodynamic therapy. Herein we report first a simple method to prepare water soluble fluorescent nano titanium oxide particles from titanium-oxo-clusters (TOCs). The nano material was characterized as an aggregate of titanium-oxo-clusters, which can be used directly in aqueous systems for investigations in biomedical fields.